2005
DOI: 10.1097/01.shk.0000190827.36406.6e
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor Is Increased During the First 48 Hours of Human Septic Shock and Correlates With Vascular Permeability

Abstract: Meningococcal septic shock is an important cause of morbidity and mortality in children and young adults worldwide and is the prototypical gram-negative septic shock. One of the key factors in the development of shock is increased microvascular permeability. Vascular endothelial growth factor (VEGF) is a central factor in angiogenesis and is an important mediator of vascular permeability. Thirteen patients with meningococcal infection (eight presenting with shock) were investigated in the early phase of invasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
98
4
8

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(121 citation statements)
references
References 26 publications
11
98
4
8
Order By: Relevance
“…For example, plasma levels of VEGF have been shown to be increased in septic patients and were related to disease severity and mortality. 39,40 In contrast in the present study, plasma VEGF levels measured 30 min after injury were unrelated to injury severity, systemic hypoperfusion and patient outcome. This finding is in accordance with previously published studies on trauma and burn patients where VEGF levels on admission were unrelated to the extent of the initial injury and not different from a healthy control group.…”
Section: Discussioncontrasting
confidence: 53%
“…For example, plasma levels of VEGF have been shown to be increased in septic patients and were related to disease severity and mortality. 39,40 In contrast in the present study, plasma VEGF levels measured 30 min after injury were unrelated to injury severity, systemic hypoperfusion and patient outcome. This finding is in accordance with previously published studies on trauma and burn patients where VEGF levels on admission were unrelated to the extent of the initial injury and not different from a healthy control group.…”
Section: Discussioncontrasting
confidence: 53%
“…In this light, two independent studies report an association between human severe sepsis/septic shock and elevated circulating levels of VEGF (26)(27). In particular Yano et a!., in a human endotoxemia model, revealed a significant increase of VEGF as early as 4 hrs from inoculation of LPS.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF is well expressed in the chronic inflammatory skin disease, psoriasis, and in synovial fluid in rheumatoid arthritis (9 -12). In addition, previous studies found an association between human severe sepsis/septic shock with elevated circulating levels of VEGF and PlGF (13,14). Using an in vitro monocyte migration assay and in vivo mouse models of arthritis, several groups, including ours, have suggested that one mechanism by which VEGF causes inflammation is by modulating the infiltration and secretion of monocytes/macrophages via the activation of VEGFR1 (11,12,15).…”
Section: Vascular Endothelial Growth Factor (Vegf)mentioning
confidence: 99%